Imaginário cultural e mitologia cristã: Nossa Senhora dos Remédios em Taubaté - Mariotto, Marcia Carolina (2016)
The devotion to Our Lady of Remedies left Portugal and landed on Brazilian soil around the eighteenth century. It came to the village of Taubaté by a route used for internal commerce, mainly gold, between Minas Gerais and the Vale do Paraíba. In Taubaté, there was a rural neighborhood called Vale do Itaim that, from the arrival of the image around 1750 and because of the great devotion raised, now it is called neighborhood Nossa Senhora dos Remédios or, as the local people say, Remédios. From the assumption that Our Lady of Remedies belongs to the cultural imagination of the local population, the purpose of this research is understand how it is constructed and how it operates religious social imaginary in the neighborhood. For this we use authors as Claude Levi-Strauss, Marcel Mauss, Mircea Eliade, Pierre Bourdieu, Michel Foucault, among others, as well as newspapers of the nineteenth century and interviews with local residents in order to see how this Christian myth and their meanings act in the system beliefs of Our Lady of Remedies neighborhood population